Distribution, deposition and spatial variability of carbon in soil using carbon and nitrogen stable isotopes - Alaswad, Fathia Ahmad M (2018)
Soil carbon (C) storage has gained much attention in the past decade due to its potentially huge impact on climate change mechanisms. However, there is still a lack of knowledge about the contribution of different C sources to soil organic carbon (SOC) formation, particularly in the subsoil. Land-use conversion to agricultural systems can affect soil C storage in terrestrial ecosystems by altering either the biotic or the abiotic processes involved in carbon cycling, such as the distribution of SOC in size at different depth of profile. The focus of this thesis was to; determine the impacts of land.-use conversion on soil carbon distribution and dynamics, as well as (2) provide an understanding of the sources of C in the investigated site. In this study, the organic carbon (OC) contents and their δ13C and δ15N stable isotopes of three soil profiles (0-30, 30-60 and 60-90 cm) under different land uses in the Selangor State in Southwest Malaysia were analyzed using (i) physical fraction of soil into different particle-size, (ii) natural abundance of the δ 13C and δ15N stable isotopes and (Ⅲ) FTIR spectroscopy. Regarding the effect of land use change on soil chemical and geo-physical properties, a two way MANOVA was used to analyses the data, with respect to spatial and depth variations, with Tukeys post-hoc tests to separate the means. Same analysis was also done for the distribution of SOC and (δ13C and δ15N) in different particle size fractions. Furthermore, Person correlation was used to determine the relationship between SOC and chemical and geo-physical properties of soil under different land use. Finally, discriminant analysis was applied to the data to predict the model of TOC (%) and SOC contents with respect to land use and depth. The results from MANOVA showed that, the conversion of secondary forest to rubber plantation caused significant decline of SOC on top soil (0-30cm). Conversely, converting rubber to oil palm plantation and pasture lead to net gain of SOC. Relative to the soil depth, the top soil 0-30 had greater contents of SOC than sub soil of 30-60 and 60-90 cm. However, in relation to δ13C & δ15N in different land use and depth, the value of δ13C was enriched by increasing the depth of profile. According of different plant species, the value of δ13C at top soil in pasture site indicted that the source of carbon in this site was from pasture δ13C (-19.38), by increasing the depth of profile, the source of carbon was attributed to rubber plantation as revealed by δ13C (-26.67) value. Interestingly, unusual value of δ15N was reported on topsoil 0-30cm, which might be a useful indicator of the source and limited level of nitrogen in the area of study. Regarding to physical fraction, the highest value of SOC, δ13C and δ15N were found in fine particles (clay and silt). Meanwhile, FTIR result revealed that, land use and soil texture plays the significant role for SOC composition. This study concluded that, the relative distribution of SOC, its fractions, carbon δ13C and nitrogen δ15N stable isotopes and FTIR absorbance can be good indicators of the soil organic matter (SOM) quantity and quality. This study therefore recommended that, conversion of rubber to other plantation has more advantage to gain more carbon rather than conversion of secondary forest to plantation, and to quantify the effects of land-use changes and soil texture on soil organic carbon distribution, carbon stored in subsoil and chemical composition of SOM should be taken into account.